2010
DOI: 10.1007/s11136-010-9763-9
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism in college students: reliability and validity of the Presenteeism Scale for Students

Abstract: These findings suggest that the PSS can be expected to be useful for assessment of students with presenteeism. Furthermore, we found that the majority of students have some health problems, and proposed that the issue of presenteeism on campus should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
5
38
0
1
Order By: Relevance
“…Despite the high self-reported health status however, 80% of participants had experienced at least one health condition over the previous 6 months and many reported a substantial decline in their health since commencing university. Health conditions reported were also similar to those found in other research, with a high incidence of allergies, asthma, respiratory infection and persistent or serious headaches [25,65]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite the high self-reported health status however, 80% of participants had experienced at least one health condition over the previous 6 months and many reported a substantial decline in their health since commencing university. Health conditions reported were also similar to those found in other research, with a high incidence of allergies, asthma, respiratory infection and persistent or serious headaches [25,65]. …”
Section: Discussionsupporting
confidence: 86%
“…Health conditions which had negatively impacted on their academic performance included: stress (29.0%); sleep difficulties (20.6%); anxiety (20.2%); and upper respiratory tract infections (15.6%). Another recent study found that almost 60% of university students had experienced a health problem in the past month, ranging from allergies and asthma, to severe headaches and insomnia [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Las investigaciones antes mencionadas se basan en estudios realizados en el sector laboral; sin embargo, existen investigaciones que han analizado como se manifiesta el presentismo en los estudiantes (Matsushita et al, 2011;Ferrito, 2016). Son escasas las investigaciones que han conceptualizado el presentismo académico.…”
Section: Introductionunclassified
“…It is thought that the proportion of university students who attend class even though they have identified health problems is not negligible [8]. In fact, we found that approximately 60% of university students had experienced some health problems that contributed to weakened academic performance, and proposed this condition as "presenteeism in students" [9] [10]. Good health care in adolescence might be crucial to decreasing the risk of absenteeism and further morbidity because many lifestyle-related health problems are formed at this phase and persist later in life [11].…”
Section: Introductionmentioning
confidence: 76%
“…Eight university students who visited the health care center for a consultation about mental health problems were enrolled in the study, and an additional 14 student volunteers were enrolled through a lecture about mental health. Of these 22 participants, 11 who had some kind of psychological problems such as depression, anxiety or emotional disorder were evaluated by the Presenteeism Scale for Students (PSS) and allocated to the "Presenteeism group" [9]. The other 11 students had no health problems and were designated as the "Control group".…”
Section: Participants and Proceduresmentioning
confidence: 99%